2020
DOI: 10.3390/insects11060352
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Occurrence and Activity of Entomopathogenic Fungi in the Algarve (Portugal) Using Different Isolation Methods

Abstract: Entomopathogenic fungi (EPF) are distributed in natural and agricultural soils worldwide. To investigate EPF occurrence in different botanical habitats and soil-ecoregions, we surveyed 50 georeferenced localities in the spring of 2016 across the Algarve region (South Portugal). Additionally, we compared three EPF isolation methods: insect baiting in untreated or pre-dried-soil and soil dilution plating on a selective medium. We hypothesized that forest habitats (oak and pine semi-natural areas) and the acidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 69 publications
(152 reference statements)
4
9
1
Order By: Relevance
“…According to the microbiological evaluation of the soil population of the two fungal species, B. bassiana could be considered a common native species in the studied locations, while B. brongniartii was never found in the untreated soil samples. This result is in line with other reports showing that B. bassiana was a dominant entomopathogenic fungal species under different soil conditions [ 66 , 67 , 68 , 69 , 70 , 71 ]. However, its detection, as well as for other entomopathogenic fungi, can be affected by the method used for the analysis [ 70 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to the microbiological evaluation of the soil population of the two fungal species, B. bassiana could be considered a common native species in the studied locations, while B. brongniartii was never found in the untreated soil samples. This result is in line with other reports showing that B. bassiana was a dominant entomopathogenic fungal species under different soil conditions [ 66 , 67 , 68 , 69 , 70 , 71 ]. However, its detection, as well as for other entomopathogenic fungi, can be affected by the method used for the analysis [ 70 ].…”
Section: Discussionsupporting
confidence: 93%
“…This result is in line with other reports showing that B. bassiana was a dominant entomopathogenic fungal species under different soil conditions [ 66 , 67 , 68 , 69 , 70 , 71 ]. However, its detection, as well as for other entomopathogenic fungi, can be affected by the method used for the analysis [ 70 ]. Considering that B. bassiana is the most widely distributed species of the whole Beauveria genus, with a wide range of parasitized species and capable of living as an endosymbiont of several plants species, its survival capacity and adaptation plasticity is not surprising [ 54 , 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…The dominance of B. bassiana in soils collected from various types of forests is also confirmed by studies conducted in Denmark [37], Finland [7], Poland [27,35,38,39], Japan [40], Italy [41,42] Spain [43,44], Austria [45], Mexico [46], Brasil [47] and Portugal [48]. Niemczyk et al [21], examining the occurrence of Beauveria spp.…”
Section: Discussionmentioning
confidence: 74%
“…Popowska-Nowak et al [ 25 ], who conducted research in various regions of Poland, showed that M. anisopliae and I. fumosorosea ( Cordyceps fumosorosea ) were the most frequently isolated species of entomopathogenic fungi from the soils of several-year-old forest nurseries, especially in the springtime, which, according to the authors, was associated with the higher humidity of the soil environment. Different research results by other authors may result from the fact that the species composition and the intensity of the occurrence of EPF in the soil are influenced by many factors, such as the content of organic matter, pH, soil type and method of its cultivation [ 7 , 8 , 9 , 21 , 47 , 48 , 68 , 69 ], as well as microclimatic conditions (temperature, humidity) and potential host density [ 36 , 68 ]. It could also be related to the methods of quantifying EPF abundance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation